Determinants of Public Administrators' Use of Performance Information: Evidence from Local Governments in Florida. (25th February 2019) - Dimitrijevska‐Markoski, Tamara; French, P. Edward
Abstract: Performance management has been a focus of scholars and practitioners for more than 25 years, yet the use of performance information has not greatly expanded as a result of this attention. Acknowledging that performance measurement is not an end in itself but rather a means to enhance focus on results and value, this article evaluates the determinants of the use of performance information by local government administrators. An online survey was administered to local government employees involved in the 2015–16 Florida Benchmarking Consortium. Analysis of the data demonstrates that institutionalization of performance measurement has the strongest statistically significant positive association with the use of performance information, followed by the design adequacy of the performance measurement system .